Hydrothermal Synthesis, Characterization and Photoluminescent Properties of a New Vanadium Substituted Keggin Assembly Supported by Ni Complex - Soussi, Imen; Aoun, Sameh; Planchat, Aurelien; Akriche, Samah (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
A new monosubstituted vanadium Keggin-type tungstophosphate derivative, [Ni(phen)3]2[PVW11O40].4H2O (phen = 1,10’-phenanthroline), has been hydrothermally synthesized and characterized by powder and single-crystal XRD methods, scanning electron microscopy (SEM), IR, UV-Vis and photoluminescence spectroscopy measurements. X-ray diffraction analysis reveals that the compound crystallizes in the monoclinic system with space group C2/c with a = 19.659 (2) Å, b = 18.054 (3) Å, c = 25.227 (4) Å and β = 100.63 (2)° and its crystal packing displays alternating [PV1W11O40(H2O)4]n4- ribbons extending along [110] and [10] respectively at z = 0 and z = ½. These ribbons are extended into a 3D supramolecular framework by hydrogen-bonding interactions generating vacant 1D-channels along c-axis leading to anchorage of transition metal complexes. Moreover, the electronic properties and the optical band gaps have also been investigated well confirming the semiconductor behavior and photoluminescent property of reported material.